An Analysis of Language Skills’ Proportion in the English Textbook Grade XII Published by Kemendikbud 2014 - Muhammad Reza Dwika Nanda; Alamsyah Harahap; Indah Damayanti (Universitas Bengkulu, 2019)
The design of this research was descritive quantitative. It was aimed to find out the suitability of english textbook with the curriculum and the proportion of the language skills’ in the English textbook grade XII published by kemendikbud 2014. The subject of this research was the English textbook grade XII for 1 year , consist of 16 chapters. The data was collected by using evaluation checklist that proposed by syllabus in curricullum 2013 and the expert (Ur (1996)). The result showed that the English Textbook Grade XII for senior high school published by Kemendikbud 2014 is categorized into “very good” category. From 27 learning objectives (KD) that proposed by the curriculum 2013 in syllabus, 22 of it is covered to the English textbook. The writing skill has the highest proportion it is 38 %; the second is reading skill has 30 %; the third is speaking skill has 21 %; and the last is listening skill has 11 %.Consequently, it can be conclude that it is suit to the standard from the government, to make the students reach the functional level of literacy and used the text – based teaching and focuss on the text.